Forensic accounting for dummies - Kass-Shraibman, Frimette; Sampath, Vijay S. (Hoboken : Wiley Pub., 2011)
Forensic accountants investigate economic crimes, perform risk assessments, assist in all kinds of civil litigation, and provide expert testimony. This hands-on guide give you plain-English explanations of the concepts and methods of forensic accounting.
Includes index.
Keywords: Forensic accounting; Fraud investigation; Fraud -- Prevention; Accounting -- United States; Fraud -- United States; Criminal investigation -- United States